Skill testing a three‐dimensional global tide model to historical current meter records. Issue 12 (17th December 2013) - Timko, Patrick G.; Arbic, Brian K.; Richman, James G.; Scott, Robert B.; Metzger, E. Joseph; Wallcraft, Alan J.
Abstract : [1] We apply several skill tests to assess tidal currents within a three‐dimensional, eddy resolving, global ocean circulation model compared to over 5000 observational velocity records spanning 40 years. We examine the skill of the HYbrid Coordinate Ocean Model (HYCOM) on a regional, basin, and global scale and in deep versus shallow water. On a global scale, we examine the model tidal kinetic energy (KE) compared to the tidal KE estimated from the observational velocity records. We examine the vertical structure of the model tidal KE by averaging over predetermined depth bins. We also investigate the ability of the model to satisfy the 95% confidence intervals of the individual tidal ellipse parameters. On a basin scale, we determine if any bias exists in model performance with regards to a particular part of the global ocean and further investigate if any variability of model skill exists within the ocean basins by testing the model against smaller subsets of the observations. Our results show that the skill of the nondata assimilative HYCOM is comparable to the skill of the altimetric‐constrained model TPXO7.2. HYCOM is shown to have up to 20% higher skill in resolving the Greenwich phase of the tides on a global basis and demonstrates moderate skill in replicating the vertical structure of the tidal currents as represented by the current meters. HYCOM demonstrates up to 20% higher skill than TPXO7.2 for some ocean basins and some ocean regions but exhibits up to 20% weaker skill in the Southern Ocean. Key Points: An objective measure of model skill in simulating 3‐D tidal currents An objective measure of model skill for tidal kinetic energy